Facial Flap Necrosis From COVID-19 Face Mask Precautions. Issue 6 (9th September 2022) - Choi, Melinda; Wo, Luccie; Joshi, Priyashma; Nugent, Ajani; Thaller, Seth R.
Abstract : Abstract: Use of facial mask coverings has been a strong Centers for Disease Control and Prevention recommendation as an essential mitigation measure in the spread of the SARS-CoV-2 novel coronavirus (COVID)-19 virus. Face mask utilization has been shown to induce changes in the skin microclimate, especially around the perioral and perinasal regions. This results in increased mask adjustments and development of friction between masks and the underlying skin. The authors report novel findings of 2 individuals with skin cancer who underwent facial reconstruction during the COVID-19 pandemic. They encountered untoward sequelae of facial flap pressure necrosis due to the use of face mask coverings. These individuals were ultimately successfully treated with local wound care. One individual experienced auricular implant extrusion and flap loss. It is critical that reconstructive surgeons be aware of potential complications and the need for potential revision surgeries due to the use of face masks, and educate their patients to properly position the protective face masks based on the type of reconstruction performed. Plastic surgeons might also reconsider reconstructive management options in light of these additional obstacles.